KONSEP RUMAH SUSUN MIKRO DI KAMPUNG TANAH MERAH, JAKARTA UTARA - Hendry Vincent Wijaya; Denny Husin (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
There are many urbanisation phenomenon in Indonesia, especially in Jakarta, that create issues of population density which have led to the emergence of large-scale settlements in big cities in the form of ‘kampung’. The aim of this project is to provide a solution to the problem of overcrowding and alternative settlements in the village in the form of micro- architecture. Kampung Tanah Merah, Koja, North Jakarta was chosen, because it has a population density, one of the highest in Jakarta. The qualitative method used by the author in this study, by observing the daily phenomena of residents. Urban acupuncture is used as a design method in this study by looking at the daily lives and behavior of local residents. Urban acupuncture methods use small-scale interventions to transform a larger urban context. The results of this study are in the form of micro housings, and other village supporting facilities. Micro housings are used by using modular units with container materials. In addition to the fulfillment of housing, the building will also be equipped with fulfillment for work and recreation, through facilities such as promenade, open space, warteg corner area and UMKM stalls. From this program, the building can support the village community to support life, work, and recreation so that the 'life, work, and fun' aspects are fulfilled in the village area. This project can answer the problems that exist in the area, so it is hoped that it can revive Kampung Tanah Merah and its surroundings. Keywords: housing; tanah merah village; micro; flats Abstrak Fenomena urbanisasi banyak terjadi di Indonesia, terutama di Jakarta, membuat isu kepadatan penduduk yang menyebabkan munculnya permasalahan pemukiman kumuh di kota-kota besar dalam wujud perkampungan. Tujuan dari proyek ini adalah untuk memberikan alternatif solusi terhadap masalah kepadatan penduduk dan pemukiman kumuh di kampung dalam bentuk mikro arsitektur. Kampung Tanah Merah, Koja, Jakarta Utara dipilih, karena memiliki tingkat kepadatan penduduk, salah satu yang tertinggi di Jakarta. Metode kualitatif digunakan penulis dalam penelitian ini, dengan mengamati fenomena keseharian warga. Urban acupuncture dipakai sebagai metode perancangan dalam penelitian ini dengan melihat keseharian dan perilaku warga sekitar. Metode urban acupuncture menggunakan intervensi skala kecil untuk mengubah konteks perkotaan yang lebih besar. Hasil pada penelitian ini adalah berupa hunian mikro, dan fasilitas penunjang kampung lainnya. Kebaruan hunian mikro yang dipakai menggunakan unit-unit modular dengan material peti kemas. Selain pemenuhan terhadap hunian, bangunan juga akan dilengkapi dengan pemenuhan akan pekerjaan, dan rekreasi, melalui fasilitas seperti promenade, open space, area warteg corner dan warung UMKM. Dari program tersebut, bangunan dapat mendukung masyarakat kampung untuk menunjang kehidupan, pekerjaan, dan rekreasi sehingga terpenuhinya aspek ‘life, work, n fun’ pada area kampung. Proyek ini dapat menjawab permasalahan yang ada pada kawasan, sehingga diharapkan dapat menghidupkan kembali Kampung Tanah Merah dan sekitarnya.